2022
DOI: 10.7759/cureus.22331
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Vaccine Hesitancy: Individual Determinants Among Saudis in Asir Region

Abstract: BackgroundCoronavirus disease 2019 (COVID-19) is a highly contagious and quickly spreading disease, especially if associated with poor awareness and unwanted behavioral practices. Unvaccinated people are at high risk of infection, mortality, and morbidity. Practices and intent toward the COVID-19 vaccine are mainly influenced by the perception of vaccine safety. This study aimed to assess the perception, practices, intent, and challenges toward the COVID-19 vaccine in Asir region, Saudi Arabia. MethodologyA qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
2
0
0
Order By: Relevance
“…Furthermore, 79.65% participants considered COVID-19 vaccines as necessary preventive measure in controlling the disease. These findings are in line with the previous study which also reported good knowledge of the participants about COVID-19 vaccination [34]. This good level of knowledge might be due to majority of educated participants in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, 79.65% participants considered COVID-19 vaccines as necessary preventive measure in controlling the disease. These findings are in line with the previous study which also reported good knowledge of the participants about COVID-19 vaccination [34]. This good level of knowledge might be due to majority of educated participants in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the authorities can take initiatives to improve awareness among unvaccinated people regarding the safety and importance of vaccines. Another Saudi Arabian study reported that the lower awareness regarding COVID-19 and vaccines can be a reason for people having low levels of knowledge 44. Our KAP study also mirrored the fact that the people who are careless about COVID-19 had poor knowledge, poor attitudes towards the variant strains, and did not follow the proper practices like a survey result in Ethiopia.…”
Section: Discussionsupporting
confidence: 70%
“…Another Saudi Arabian study reported that the lower awareness regarding COVID-19 and vaccines can be a reason for people having low levels of knowledge. 44 Our KAP study also mirrored the fact that the people who are careless about COVID-19 had poor knowledge, poor attitudes towards the variant strains, and did not follow the proper practices like a survey result in Ethiopia. In that survey, the authors observed that the people who did not have access to the TV were associated with poor practice.…”
Section: Discussionmentioning
confidence: 53%